2012
DOI: 10.1002/adma.201202447
|View full text |Cite
|
Sign up to set email alerts
|

Hypercrosslinked Aromatic Heterocyclic Microporous Polymers: A New Class of Highly Selective CO2 Capturing Materials

Abstract: Aromatic heterocyclic microporous polymers with high surface areas are obtained by directly crosslinking of the heterocyclic monomers under mild conditions. Owing to the narrow pore system and the heteroatom-rich pore surface, these networks exhibit high CO(2) adsorption capacity and selectivity. At 273 K, the CO(2)/N(2) selectivity of Py-1 is about 117, which is among the highest the reported microporous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
281
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(293 citation statements)
references
References 53 publications
6
281
2
4
Order By: Relevance
“…At the onset of adsorption, the heat of adsorption of CO 2 was 30, 29, 33 and 32 kJ mol −1 for CTF‐HUST‐1, CTF‐HUST‐2, CTF‐HUST‐3, and CTF‐HUST‐4, respectively (Figure S11b), which is in a good range for CO 2 capture applications and higher than reported for CTF‐1 (27.5 kJ mol −1 ) 11. Indeed, the CO 2 adsorption heat for these CTF‐HUSTs is higher than for most other nitrogen‐rich porous organic frameworks, including porous benzimidazole polymers,12 electron‐rich organonitridic frameworks,13 conjugated microporous polymers,14 and hypercross‐linked polymers 15…”
mentioning
confidence: 95%
“…At the onset of adsorption, the heat of adsorption of CO 2 was 30, 29, 33 and 32 kJ mol −1 for CTF‐HUST‐1, CTF‐HUST‐2, CTF‐HUST‐3, and CTF‐HUST‐4, respectively (Figure S11b), which is in a good range for CO 2 capture applications and higher than reported for CTF‐1 (27.5 kJ mol −1 ) 11. Indeed, the CO 2 adsorption heat for these CTF‐HUSTs is higher than for most other nitrogen‐rich porous organic frameworks, including porous benzimidazole polymers,12 electron‐rich organonitridic frameworks,13 conjugated microporous polymers,14 and hypercross‐linked polymers 15…”
mentioning
confidence: 95%
“…Hypercross-linked polymers represent a new class of porous materials that are prepared mainly by a Friedel-Crafts alkylation reaction [28][29][30] . The permanent porosity in hypercross-linked polymers is a result of extensive cross-linking reactions, which prevent the polymer chains from collapsing into a dense, non-porous state [31][32][33] .…”
mentioning
confidence: 99%
“…The images indicate the formation of amorphous particles with a size of approximately 50-100 nm in diameter, which is similar to other types of hyper-crosslinked polymers. 17,24 Further analysis of the polymers by thermogravimetric analysis (TGA) showed that the sample has great thermal stability with a thermal decomposition temperature over 550 C ( Fig. S3 †) due to the strong covalent bonding in the network.…”
Section: Characterization Of Adsorbentsmentioning
confidence: 99%